Early and exudative age‐related macular degeneration is associated with increased plasma levels of soluble TNF receptor II. (2nd November 2014) - Faber, Carsten; Jehs, Tina; Juel, Helene Bæk; Singh, Amardeep; Falk, Mads Krüger; Sørensen, Torben Lykke; Nissen, Mogens Holst
Abstract Purpose We have recently identified homeostatic alterations in the circulating T cells of patients with age‐related macular degeneration (AMD). In cultures of retinal pigment epithelial cells, we have demonstrated that T‐cell‐derived cytokines induced the upregulation of complement, chemokines and other proteins implicated in AMD pathogenesis. The purpose of this study was to test whether increased plasma levels of cytokines were present in patients with AMD. Methods We conducted a case–control study. Age‐related macular degeneration status was assessed using standardized multimodal imaging techniques. Plasma was isolated from freshly drawn peripheral venous blood samples and analysed for interleukin (IL)15, IL18, interferon (IFN)γ, soluble tumour necrosis factor (TNF) receptor II (sTNFRII) and complement factor H (CFH) Y402H genotype. Results We included 136 individuals with early or late forms of AMD and 74 controls. Significantly increased levels of sTNFRII were observed in patients with early or exudative AMD (p < 0.01). After adjusting for CFH Y402H genotype, age, sex and smoking history, the level of sTNFRII remained a significant predictor for prevalence of AMD with odds ratios at 3.0 in the middle and 3.6 in the highest tertiles. Levels of IL15, IL18 and IFNγ were low and not associated with AMD. Conclusions Increased plasma level of sTNFRII is found to be associated with AMD. The data supports the observations of low‐grade, systemic inflammatory alterations in patients with AMD. However, it remains to be determined whether increased levels of TNFα can be found, which directly reflects an increased activity of macrophages and T cells.